Approaches to Meaning in Music - Almén, Byron; Pearsall, Edward (Bloomington Indiana University Press, 2006)
Approaches to Meaning in Music presents a survey of the problems and issues inherent in pursuing meaning and signification in music, and attempts to rectify the conundrums that have plagued philosophers, artists, and theorists since the time of Pythagoras. This collection brings together essays that reflect a variety of diverse perspectives on approaches to musical meaning. Established music theorists and musicologists cover topics including musical aspect and temporality, collage, borrowing and association, musical symbols and creative mythopoesis, the articulation of silence, the mutual interaction of cultural and music-artistic phenomena, and the analysis of gesture.Contributors are Byron Almén, J. Peter Burkholder, Nicholas Cook, Robert S. Hatten, Patrick McCreless, Jann Pasler, and Edward Pearsall.